A new measurement of the leading hadronic corrections to the muon g-2* - Trentadue Luca (EPJ Web of Conferences, 2016)
A novel approach to determine the leading hadronic corrections to the muon g-2 is proposed. It consists in a measurement of the effective electromagnetic coupling in the space-like region. This method may become feasible at flavor factories resulting in a determination potentially competitive with the dispersive approach via time-like data.